A taxonomic study of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from China, with two new species and three new records - Qin, Jiong; Chen, Bin; Li, Ting-Jing (Zootaxa, 2024)
In this paper, two new species, namely Antepipona foveapronota Qin, Chen & Li, sp. nov. from Hainan (China) and A. xinjiangensis Qin, Chen & Li, sp. nov. from Xinjiang (China) are described and illustrated. A. varentzowi (Morawitz, 1895), A. luzonensis (Rohwer, 1919), and A. curialis (Morawitz, 1895) are newly recorded from China. In addition, the infrequent species A. tylocifica Kurzenko, 1977 is also redescribed. A key to the Chinese species of the genus Antepipona is provided.